The polarization observables T, P, and H and their impact on γp→pπ0 multipoles - J. Hartmann (Physics Letters B, 2015)
Data on the polarization observables T, P, and H for the reaction γp→pπ0 are reported. Compared to earlier data from other experiments, our data are more precise and extend the covered range in energy and angle substantially. The results were extracted from azimuthal asymmetries measured using a transversely polarized target and linearly polarized photons. The data were taken at the Bonn electron stretcher accelerator ELSA with the CBELSA/TAPS detector. Within the Bonn-Gatchina partial wave analysis, the new polarization data lead to a significant narrowing of the error band for the multipoles for neutral-pion photoproduction.